NOVITIATE FORMATION: A THEOLOGICO-CANONICAL STUDY OF CANON 646 IN CONTEMPORARY RELIGIOUS LIFE - Mathew, Regi (Asian Horizons, 2016)
The dissertation on the nature and purpose of the novitiate formation centres its research on canon 646 of Codex Iuris Canonici (CIC) 1983. In order to obtain a comprehensive understanding of the topic, while treating the canonical aspects of the novitiate, the thesis also examines the theological importance of formation in religious life with a specific focus on the contemporary novitiate formation and its challenges. Using a narrative, analytical, synthetic, and interdisciplinary method, the study enquires into the purpose of the novitiate formation from the early history of religious life until the present day. The thesis is an attempt to understand the role and relevance of novitiate in the challenging situations of the contemporary religious life.